2022
DOI: 10.3390/antibiotics11121843
|View full text |Cite
|
Sign up to set email alerts
|

The Blood–Brain Barrier and Pharmacokinetic/Pharmacodynamic Optimization of Antibiotics for the Treatment of Central Nervous System Infections in Adults

Abstract: Bacterial central nervous system (CNS) infections are serious and carry significant morbidity and mortality. They encompass many syndromes, the most common being meningitis, which may occur spontaneously or as a consequence of neurosurgical procedures. Many classes of antimicrobials are in clinical use for therapy of CNS infections, some with established roles and indications, others with experimental reporting based on case studies or small series. This review delves into the specifics of the commonly utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 208 publications
1
12
1
Order By: Relevance
“…9,21,22 Historically, greater inflammation in the CNS has been thought to be a catalyst for drug penetration across blood-brain and blood-CSF barriers. 17 The present study found little relationship between CSF drug concentrations and pro-inflammatory cytokines. While elevated CSF concentrations of cytokines does not necessarily indicate increased meningeal inflammation, the findings do suggest that the relationship between CSF drug concentrations and inflammation is minimal.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…9,21,22 Historically, greater inflammation in the CNS has been thought to be a catalyst for drug penetration across blood-brain and blood-CSF barriers. 17 The present study found little relationship between CSF drug concentrations and pro-inflammatory cytokines. While elevated CSF concentrations of cytokines does not necessarily indicate increased meningeal inflammation, the findings do suggest that the relationship between CSF drug concentrations and inflammation is minimal.…”
Section: Discussioncontrasting
confidence: 77%
“…Antibiotic penetration into the CSF is generally thought to be increased when there is a breakdown in the blood-brain barrier due to meningeal inflammation in persons with TBM. 17 We therefore sought to mine concomitantly collected high-resolution metabolomics and cytokine data to determine whether any soluble immune mediators were associated with CSF drug concentrations. We used mixed effects linear models to determine which cytokines and metabolites with known chemical identities were most strongly associated with CSF concentrations of each antibiotic.…”
Section: Resultsmentioning
confidence: 99%
“…Doxycycline is a tetracycline antibiotic derivative that is readily used in humans, making it relevant for in vivo application. It has been shown to cross the blood-brain barrier, thus enabling it to act on cells that have been grafted into the CNS [33][34][35]. Therefore, in vivo doxycycline treatment can alter cell fate to overcome the complex signaling cascades within the host microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cases of vancomycin-resistant enterococcal meningitis/ventriculitis have been described in the literature. There are limited therapeutic options for device-associated vancomycin-resistant CNS infections, and the optimal treatment has yet to be discovered [22][23][24][25][26][27]. An antibiotic's entrance into the CSF is determined by the drug's physicochemical qualities, alongside host variables such as the patient's age, CSF flow and volume, plasma albumin, and polymorphisms in genes that encode transport proteins [22].…”
Section: Discussionmentioning
confidence: 99%